2016
DOI: 10.1371/journal.pone.0166266
|View full text |Cite
|
Sign up to set email alerts
|

PD-L1 Status in Refractory Lymphomas

Abstract: Targeted immunotherapy based on PD-1/PD-L1 suppression has revolutionized the treatment of various solid tumors. A remarkable improvement has also been observed in the treatment of patients with refractory/relapsing classical Hodgkin lymphoma (cHL). We investigated PD-L1 status in a variety of treatment resistant lymphomas. Tumor samples from 78 patients with therapy resistant lymphomas were immunohistochemically (IHC) investigated for the expression of PD-L1 using two antibody clones (SP142 and SP263, Ventana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
47
1
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(55 citation statements)
references
References 28 publications
3
47
1
4
Order By: Relevance
“…In lymphoid malignancies, PD-L1 expression is detected variably not only in lymphoma cells but also in the immune cells of the microenvironment, best exemplified by tissue macrophages. [2][3][4][5][6][7][8] Of note, previous studies have shown that PD-L1 was expressed frequently in classical (C) Hodgkin lymphoma (HL), primary mediastinal large B cell lymphoma and Epstein-Barr virus (EBV)-associated lymphomas, including EBV + diffuse large B cell lymphoma (DLBCL) of not otherwise specified (NOS) type and extranodal natural killer (NK)/T cell lymphoma of nasal type (EBV + ) 9 in the World Health Organisation (WHO) 2016 classification. 10 This overexpression was activated by genetic alterations affecting the PD-L1 locus in the tumour cells or by viral infection that induces immune tolerance.…”
Section: Introductionmentioning
confidence: 99%
“…In lymphoid malignancies, PD-L1 expression is detected variably not only in lymphoma cells but also in the immune cells of the microenvironment, best exemplified by tissue macrophages. [2][3][4][5][6][7][8] Of note, previous studies have shown that PD-L1 was expressed frequently in classical (C) Hodgkin lymphoma (HL), primary mediastinal large B cell lymphoma and Epstein-Barr virus (EBV)-associated lymphomas, including EBV + diffuse large B cell lymphoma (DLBCL) of not otherwise specified (NOS) type and extranodal natural killer (NK)/T cell lymphoma of nasal type (EBV + ) 9 in the World Health Organisation (WHO) 2016 classification. 10 This overexpression was activated by genetic alterations affecting the PD-L1 locus in the tumour cells or by viral infection that induces immune tolerance.…”
Section: Introductionmentioning
confidence: 99%
“…Eine PD-L1-Expression (häufig liegt der gewählte Schwellenwert bei 5%) findet sich bei einer Untergruppe von DLBCL-Zelllinien, hauptsächlich vom ABC-Phänotyp [29], und überwiegend in Primärproben von Patienten mit ABC-DLBCL [30], bei denen eine Amplifikation des PD-L1/L2-Locus nachgewiesen wurde [31]. In einer großen Serie zeigten jedoch nur 80 von 260 Patientenproben eine PD-L1-Expression [32], und dies wiederum besonders deutlich in der Nicht-GCB-Gruppe; in anderen Untersuchungen wurde eine Expression von etwa 50% festgestellt [33]. Vorläufige univariate Daten und sogar einige komplexere Modelle weisen auf eine potenzielle Korrelation zwischen PD-L1-Expression und einer schlechten Prognose hin [34,35] …”
Section: Diffuses Großzelliges B-zell-lymphomunclassified
“…Zwar wurden in klinischen Studien, in denen kombinierte intensivierte Therapieelemente zur Anwendung kamen, Langzeit-Remissionen beobachtet, doch zeigen die unter realen Bedingungen gewonnenen Daten ein medianes Gesamtüberleben von weniger als 3 Jahren [58]. Selten oder nie wurde bei MCL-Zellen eine PD-L1-Positivität nachgewiesen [33,46]. In die von Lesokhin et al [37] veröffentlichte Studie wurden 4 Patienten mit MCL eingeschlossen, von denen keiner auf die Behandlung ansprach.…”
Section: Mantelzelllymphomunclassified
“…PD-L1 expression (a threshold of 5% is frequently chosen) can be found in a subset of DLBCL cell lines, mainly of the ABC phenotype [29] and predominantly in primary samples of patients with ABC-DLBCL [30], where amplifications of the PD-L1/L2 locus have been found [31]. However, in a large series, only 80 out of 260 patient samples showed PD-L1 expression [32], again pronounced in the non-GCB group; others have found approximately 50% expression [33]. Preliminary univariate data or even some more complex models show a potential correlaHeß Oncol Res Treat 2017;40:662-672 664 tion of PD-L1 expression with a dismal prognosis [34,35]; however, this has not been proven in prospective trials.…”
Section: Aggressive Lymphomas Diffuse Large-b Cell Lymphomamentioning
confidence: 99%
“…Although long-term remissions have been observed within clinical trials combining intensive treatment elements, real-world data show a median overall survival of less than 3 years [58]. PD-L1 has never or rarely been shown to be positive in MCL cells [33,46].…”
Section: Mantle Cell Lymphomamentioning
confidence: 99%